Thea Stilton and the Spanish dance mission - Stilton, Thea.; Balleello, Chiara; Verzini, Daniele (New York : Scholastic, 2013)
The Thea Sisters are visiting friends in Spain when a mysterious theft turns their trip into an investigation! They end up hot on the trail of a secret treasure. The mouselets are in for an incredible adventure full of flamenco dance!.
"Geronimo Stilton."
2nd-4th graders.
Grade 4.
Keywords: Stilton, Thea (Fictitious character) -- Juvenile fiction; Mice -- Juvenile fiction; Theft -- Juvenile fiction; Stilton, Thea (Fictitious character) -- Fiction; Mice -- Fiction; Stealing -- Fiction; Mice; Stilton, Thea (Fictitious character); Theft; Spain -- Juvenile fiction; Spain -- Fiction; Spain; Mystery and detective stories; Fiction; Juvenile works; Mystery fiction